Early Bronze Age burial mounds in Avan - Muradyan, Firdus (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The necropolis is situated in the district of Avan built in the northeastern outskirts of Yerevan in 1970-80s. During the conservation works conducted there in 1987 a burial mound with the materials characteristic of the early stages of the Kura-Araxes culture was opened. In 2012 two other burial mounds of the Early Bronze Age has been unearthed in this necropolis.